2016
DOI: 10.17159/2310-3833/2016/v46n2a2
|View full text |Cite
|
Sign up to set email alerts
|

Expert opinion on splinting adult patients with neurological injuries

Abstract: In the light of a lack of research evidence, this study explored expert opinion for splinting in adults with neurological injuries. An exploratory, descriptive, qualitative methodology was used with 14 occupational therapists, experienced in neuro-rehabilitation. Data were analysed based on a priori themes from two models of clinical practice:- • The Model of Practice Development: - themes indicate that most value was placed on personal knowledge gained from experience in the field and being able to individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…The components highlighted by Chazen and Franzsen (2016) support the work of Kuipers et al (2006) and Rassafiani et al (2008) who highlighted factors relating to the client, the therapist and the environment, all of which could fall under each type of clinical reasoning. Chazen and Franzsen (2016) further highlighted that effective splinting for neurological conditions is dependent on a clear understanding of the client's background and context, and that a problem-solving process be utilised to consider all factors in order for splinting to be effective. These authors provide insight into the clinical reasoning employed when working with clients with ABI and splinting, However, their study results are not generalisable to the larger South Africa context given the limitation of the small homogenous sample of practitioners working in private practice and academia in one province.…”
Section: Literature Reviewmentioning
confidence: 89%
See 2 more Smart Citations
“…The components highlighted by Chazen and Franzsen (2016) support the work of Kuipers et al (2006) and Rassafiani et al (2008) who highlighted factors relating to the client, the therapist and the environment, all of which could fall under each type of clinical reasoning. Chazen and Franzsen (2016) further highlighted that effective splinting for neurological conditions is dependent on a clear understanding of the client's background and context, and that a problem-solving process be utilised to consider all factors in order for splinting to be effective. These authors provide insight into the clinical reasoning employed when working with clients with ABI and splinting, However, their study results are not generalisable to the larger South Africa context given the limitation of the small homogenous sample of practitioners working in private practice and academia in one province.…”
Section: Literature Reviewmentioning
confidence: 89%
“…As and when a client progresses through the stages of motor recovery, the use of the splint and its purpose should be continually re-evaluated. As reflected in the results of this study, splints are used more in the earlier stages of motor recovery than the later stages., and it can be noted that once the client starts to show recovery, the splint should either be removed or it should be adjusted to enhance functional use of the hand and upper limb in daily activities (Chazen and Franzsen, 2016;Gillen, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepworth et al [ 30 ] found that hand splinting in children with a neurological impairment requires knowledge of the condition (92.5%), experience (82.5%), competency (80%), and available resources (75%). Similarly, Chazen and Franzsen [ 33 ] evaluated the opinion of experts regarding splinting adult patients with neurological conditions, who reported that occupational therapists should develop skills in fabricating splints and learn from others’ experiences with clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate splinting guidelines should not be rigidly prescriptive, but instead stem from a conceptual, clinical, and reasoning framework. Therapists with less clinical experience may seek out and follow established splint protocols, while more experienced therapists are more likely to create individualized splinting programs [12]. Clinical decision making references practice guidelines, but it is critical to realize each client is unique.…”
Section: Discussionmentioning
confidence: 99%